Imaging-Related Risk Factors for Bleeding Complications of US-Guided Native Renal Biopsy: A Propensity Score Matching Analysis - Li, Qian; Lin, Xueying; Zhang, Xi; Samir, Anthony E.; Arellano, Ronald S. (Journal of vascular and interventional radiology, 2019)
To evaluate imaging-related hemorrhagic risk factors for ultrasound (US)-guided native kidney biopsy. A retrospective review was conducted of adult patients who underwent US-guided native kidney biopsy at a single center between January 2006 and March 2016 and identified 37 of 551 patients (6.72%) with postbiopsy bleeding complications, including 11 major complications (2.00%; n = 11) and 26 minor complications (4.72%; n = 26). Ten patients with major complications and 20 with minor complications were matched with 20 control subjects each by propensity score matching based on age, needle size, number of cores, blood pressure, partial thromboplastin time, prothrombin time, platelet count, and estimated glomerular filtration rate. Biopsy needle passing through the renal sinus was identified in the patients with major (6 of 10; 60%) and minor complications (8 of 20; 40.0%) but not in the control groups. For patients with major complications, the needle–sinus distance was significantly shorter (5.11 mm ± 7.32 vs 11.14 mm ± 3.54; P = .023) and the needle–capsule distance was significantly longer (17.52 mm ± 8.04 vs 9.28 mm ± 3.29; P = .0004) than in control subjects. The bimodal distribution of cortical tangential angles (< 30° or ≥ 60°) in minor complication cases (17 of 20; 85.0%) was significantly greater than in the control group (8 of 20; 40.0%; odds ratio = 8.50; P = .004). This study identifies imaging risk factors in US-guided native kidney biopsy and recommends an algorithm to manage them, including appropriate needle path position between the renal capsule and sinus and proper needle cortical tangential angle.